1983
DOI: 10.1063/1.525855
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation properties of the imperfect Bose gas

Abstract: The fluctuations of the occupation numbers of the different levels of the imperfect Bose gas are computed. They are neither normal, Gaussian, nor independent of the way the infinite volume limit is taken. The fluctuations of the overall density are on the contrary normal, Gaussian, and shape independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 7 publications
2
69
0
Order By: Relevance
“…(a) Since the paper by Buffet and Pulé [5] it has been known that there are differences in the fluctuations of the PBG condensate in the canonical and grand-canonical ensembles. We have shown that the picture becomes even more complicated if one passes to the case of Casimir boxes where there is already generalized BEC in the GCE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) Since the paper by Buffet and Pulé [5] it has been known that there are differences in the fluctuations of the PBG condensate in the canonical and grand-canonical ensembles. We have shown that the picture becomes even more complicated if one passes to the case of Casimir boxes where there is already generalized BEC in the GCE.…”
Section: Resultsmentioning
confidence: 99%
“…But first we give some results which will be useful in all three cases. The basic identity for the canonical expectations at density ρ = n/V of the occupation numbers is (see [5] equation (10)):…”
Section: Generalized Bose-einstein Condensation and Fluctuations Of Tmentioning
confidence: 99%
See 2 more Smart Citations
“…The ground state energy density reads e g.s. = t − |b|dρs q (33) where s q = lim S(q j )/V (for any j).…”
Section: A Mean-field Model For Coherent Supersolidsmentioning
confidence: 99%